2012
DOI: 10.1161/atvbaha.112.247866
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Angiopoietin-Like Protein 2 Accelerates Development of Abdominal Aortic Aneurysm

Abstract: Objective-Recently, we reported that angiopoietin-like protein 2 (Angptl2) functions in various chronic inflammatory diseases. In the present study, we asked whether Angptl2 and its associated chronic inflammation contribute to abdominal aortic aneurysm (AAA). Methods and Results-Immunohistochemistry revealed that Angptl2 is abundantly expressed in infiltrating macrophages within the vessel wall of patients with AAA and in a CaCl 2 -induced AAA mouse model. When Angptl2-deficient mice were used in the mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 40 publications
7
102
0
Order By: Relevance
“…Our previous report showing chronic inflammation in skin tissue of K14-Angptl2 Tg mice demonstrated infiltration of skin tissue by inflammatory cells, including activated macrophages and neutrophils (7), both of which are sources of ROS (36). Angptl2 reportedly activates NFkB proinflammatory signaling in various cell types (3)(4)(5)(6)(7)37), which also enhances ROS production (38). Taken together, Angptl2 secreted from skin tissue of K14-Angptl2 Tg mice may increase ROS production due to activity of infiltrated and activated inflammatory cells.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous report showing chronic inflammation in skin tissue of K14-Angptl2 Tg mice demonstrated infiltration of skin tissue by inflammatory cells, including activated macrophages and neutrophils (7), both of which are sources of ROS (36). Angptl2 reportedly activates NFkB proinflammatory signaling in various cell types (3)(4)(5)(6)(7)37), which also enhances ROS production (38). Taken together, Angptl2 secreted from skin tissue of K14-Angptl2 Tg mice may increase ROS production due to activity of infiltrated and activated inflammatory cells.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we reported that 9 months of CAT magnified 50-folds the rise in COX2 expression associated with aging in the mouse aorta [26]. Angptl2, on the other hand, is associated with inflammation as its presence is increased in patients with rheumatoid arthritis and abdominal aortic aneurysm [47,69], while its deletion can lower pro-inflammatory cytokines in rodents [67,69]. Hence, our results suggest that early CAT treatment induces a pro-inflammatory environment upon the challenge of a WD: we propose that CAT limited the development of antioxidant defense mechanisms able to counteract the stress induced by the WD.…”
Section: Inflammationmentioning
confidence: 96%
“…ANGPTL2 and Heart Disease secreted ANGPTL2 also accelerates atherosclerotic disease in mice (Figure 4). 55 Thus, ANGPTL2-induced chronic inflammation predisposes individuals to atherosclerotic disease and to CAD development. Furthermore, inflammation also underlies plaque destabilization.…”
Section: Angptl2 Function In Obesity and Associated Metabolic Diseasesmentioning
confidence: 99%